Labor Of Dionysus : A Critique of the State-Form - Hardt, Michael (Book collections on Project MUSE., 1990)
Labor is the living, form-giving fire,? Marx wrote.?It is the transitoriness of things, their temporality, as their transformation by living time.? How is it, then, that labor, with all its life-affirming potential, has become the means of capitalist di.